Semiconductor sensors for dosimetry of epithermal neutrons - Litovchenko, P.G.; Moss, R.; Stecher-Rasmussen, F.; Appelman, K.; Barabash, L.I.; Kibkalo, T.I.; Lastovetsky, V.F.; Litovchenko, A.P.; Pinkovska, M.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Minimum energy of neutron to displace atoms in silicon crystals are equal to 200 eV. Due to this fact testing our p-i-n diodes under irradiation by the epithermal neutrons was carried out. The more advanced p-i-n diodes on the base of high purity silicon were used at present work, and, as a result, we have obtained considerably more sensitive sensors for more wide range of neutron doses. The sensitivity of sensors is 0.14 V/Gy for average neutron energy of 24 keV.